2017
DOI: 10.7150/thno.18290
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota-Mediated Personalized Treatment of Hyperlipidemia Using Berberine

Abstract: Nitroreductases (NRs) are bacterial enzymes that reduce nitro-containing compounds. We have previously reported that NR of intestinal bacteria is a key factor promoting berberine (BBR) intestinal absorption. We show here that feeding hamsters with high fat diet (HFD) caused an increase in blood lipids and NR activity in the intestine. The elevation of fecal NR by HFD was due to the increase in either the fraction of NR-producing bacteria or their activity in the intestine. When given orally, BBR bioavailabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 41 publications
(65 reference statements)
0
72
0
1
Order By: Relevance
“…Increased dietary protein, leading to increased arginine, could thus constitute a potential dietary intervention to improve digoxin efficacy. Recent data have also elucidated the role of diet‐induced changes in the gut microbiota on the oral bioavailability of the herbal supplement, berberine, used for the treatment of hyperlipidaemia and type 2 diabetes (Wang et al ., ). The bioavailability of berberine was significantly increased in high‐fat diet (HFD)‐fed hamsters in comparison to hamsters fed a normal diet.…”
Section: Gut Microbiota–drug Interactionsmentioning
confidence: 97%
“…Increased dietary protein, leading to increased arginine, could thus constitute a potential dietary intervention to improve digoxin efficacy. Recent data have also elucidated the role of diet‐induced changes in the gut microbiota on the oral bioavailability of the herbal supplement, berberine, used for the treatment of hyperlipidaemia and type 2 diabetes (Wang et al ., ). The bioavailability of berberine was significantly increased in high‐fat diet (HFD)‐fed hamsters in comparison to hamsters fed a normal diet.…”
Section: Gut Microbiota–drug Interactionsmentioning
confidence: 97%
“…Nutraceuticals containing BBR can significantly reduce plasma LDL-C levels of elderly statinintolerant hypercholesterolemic patients (Marazzi et al, 2011). Another study showed that when it plus low-dose statins and/or ezetimibe, most coronary artery disease (CHD) patients who were high-dose statin intolerant could achieve target LDL-C levels within 3 to 6 months (Marazzi et al, 2019).Of note, the therapeutic effects of BBR on these inflammatory and metabolic diseases, such as emergent mild diarrhea (Yue et al, 2019), ulcerative colitis (Cui et al, 2018), obesity (Xie et al, 2011;Zhang et al, 2015), hyperlipidemia (Wang et al, 2017) and diabetes , appeared to be related to the regulation of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, E. coli infection was observed to significantly reduce the absorption of orally administered enrofloxacin in broilers (Guo et al, 2014). Yan Wang reported that berberine treatment lowered blood lipids and glucose effectively only in the high-fat diet (HFD)-fed hamsters with increased levels of nitrate reductase (NR) activity in the gut microbiota (Wang et al, 2017). In our previous research work, liver injury affects the gut microbiome in rats, particularly by depleting the Lactobacillus, which is directly involved in the bioconversion of the GL.…”
Section: Discussionmentioning
confidence: 99%
“…Rats pretreated with L. murinus or normal saline (n = 6) were administered an oral (10 mg/kg) dose of GL dissolved in 0.5% sodium carboxymethyl cellulose (CMC-Na) (5 mg/ml) 24 h after completing the seven consecutive daily treatment with physiological saline (control) or L. murinus dissolved in physiological saline (1 × 10 9 CFU/mouse). Whole-blood samples were taken from the orbital vein into tubes with heparin sodium at 0.17, 0.33, 0.5, 0.75, 1, 2, 4, 6, 8, 12, 24, 48, 72 h after oral administration (Zhou et al, 2013;Wang et al, 2017). Plasma was harvested by centrifugation at 8,000 rpm for 10 min and stored at −20 • C until analyzed.…”
Section: Pharmacokinetic Experimentsmentioning
confidence: 99%